2020
DOI: 10.3390/en13061510
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle-to-Grid in Standard and Fast Electric Vehicle Charging: Comparison of Renewable Energy Source Utilization and Charging Costs

Abstract: Croatia aims to achieve 10% of its energy production from the renewable energy sources in the total energy consumption in the transport sector. One of the ways to achieve this goal is by the use of electric vehicles. This work comparatively analyses the financial and social aspects of vehicle-to-grid charging in standard and fast charging mode, their impact on the renewable electricity production and the total electricity consumption regulated through variable electricity prices. Data were taken for the wider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Reference 12 points out that several public tier‐II charging stations in Germany adopted values for charging electric vehicles around the US $0.28/kWh in 2011. Also, the author applied a study model that considers charging for EVs on a regulated basis through a current electricity price set and found electricity prices around 0.12 to 0.29 US $/kWh.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference 12 points out that several public tier‐II charging stations in Germany adopted values for charging electric vehicles around the US $0.28/kWh in 2011. Also, the author applied a study model that considers charging for EVs on a regulated basis through a current electricity price set and found electricity prices around 0.12 to 0.29 US $/kWh.…”
Section: Resultsmentioning
confidence: 99%
“…In Reference 11, studies show that alternative sources used in conjunction with the grid can bring benefits both at the environmental level and in terms of the energy capacity of the system while assisting in minimizing the costs for the consumer. In Reference 12, the authors analyzed the impact of fast and standard EV charging on demand, considering financial and social aspects and the regulation of EV charging through the price of electricity. The authors of Reference 13 present a way to combine several strategies, such as a load scheduler, demand‐side management, vehicle‐to‐grid (V2G) generation systems, and renewable energy, to reduce the annual electricity bill of a residential microgrid based on a dual tariff scheme.…”
Section: Introductionmentioning
confidence: 99%
“…The cooperation of the peak shaving effect of battery energy storage and thermal storage electric boiler coordinated operation is of great significance for the safe and stable operation of wind power [26]. Flexible electric vehicle charging mode is conducive to the renewable energy utilization [27]. The effect of the superconducting fault current limiter (SFCL) on an electric power grid with the wind-turbine generation is also analyzed [28].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies also claim that V2G technology does not result in an overall cost decrease. The future financial and social consequences of standard and fast charging in a V2G context, including renewable energy production, were studied in [6]. Other than expected, they found that fast charging led to a lower utilization of electricity generated by RES and did not result in a significant reduction of charging costs [6].…”
Section: Introductionmentioning
confidence: 99%